Lyophilized Composite Loaded with Meloxicam-Peppermint oil Nanoemulsion for Periodontal Pain - Sindi, Amal M. (Polymers (Basel), 2021)
Maintaining oral health helps to prevent periodontal inflammation and pain, which can progress into more detrimental issues if left untreated. Meloxicam (MX) is a commonly used analgesic for periodontal pain, but it can have adverse gastrointestinal effects and poor solubility. Therefore, this study aimed to enhance the solubility of MX by developing a self-nanoemulsifying drug delivery system (SNEDDS). Considering the anti-ulcer activity of peppermint oil (PO), it was added in a mixture with medium-chain triglyceride (MCT) to the MX-loaded SNEDDS formulation (MX-PO-SNEDDS). After optimization, MX-PO-SNEDDS exhibited a PO:MCT ratio of 1.78:1, surfactant mixture HLB value of 14, and MX:oil mix ratio of 1:15, a particle size of 47 ± 3 nm, stability index of 85 ± 4%, ex vivo J(ss) of 4 ± 0.6 μg/cm(2)min, and ulcer index of 1 ± 0.25 %. Then, orally flash disintegrating lyophilized composites (MX-SNELCs) were prepared using the optimized MX-PO-SNEDDs. Results reveal that MX-SNELCs had a wetting time of 4 ± 1 s and disintegration time of 3 ± 1 s with a high in vitro MX release of 91% by the end of 60 min. The results of pharmacokinetic studies in human volunteers further demonstrated that, compared to a marketed MX tablets, MX-SNELCs provided a higher C(max), T(max), and AUC and a relatively greater bioavailability of 152.97 %. The successfully developed MX-SNELCs were found to be a better alternative than the conventional tablet dosage form, thus indicating their potential for further development in a clinically acceptable strategy for managing periodontal pain.